Active thermal control system for nano-satellites - Karthikeyan Baskaran (2015)
Satellites are subjected to various types of thermal loads or radiative loads while in orbit. The evolution of reduction in the size of the satellites led to few important requirements which intend to reduction in size and mass of their subsystems. As a result a device has to be designed in order to cater the radiative thermal loads with reduced mass and size. This can be achieved using an electrochromic device. Electrochromic devices are capable of altering their optical properties when a certain potential is applied. Most basic electrochromic devices consists of active reflective electrode, ion conducting and an ion storage layers. The materials used as active electrode are mainly metal oxides of very small thickness. The electrolyte is the ion conducting layer which can be conducting polymers or inorganic protons or positive ions that can intercalated and de-intercalated with the active layer which are bonded as half cells with active layer and ion conductor. The present work investigates all thin film electrochromic device made of inorganic oxides. Polymeric electrolytes are not suitable for space environment that might outgas and contaminate the substrate over which it is coated. The emissivity variation of two different samples made of LiPC liquid electrolyte and Ta205 Solid electrolyte with the c-W03 as active electrochromic layer are found in the MIR and FIR region (2 - 25 11m). The substrate is Al6061 and ITO over glass acted as top contacts. The emissivity variation achieved is between 0.7-0.82 and 0.23-0.29 at 300K using FTIR Spectrometer. Such property of modulating emissivity makes electrochromic devices as strong contenders to other existing active thermal control devices for small satellites.